Acute respiratory distress syndrome (ARDS): An evidence-based management - Nipatta, Phuttaphong (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 2 (2019): April-June 2019DO - 10.14456/nujst.2019.19, 2019)
Acute respiratory distress syndrome (ARDS) is a common acute respiratory failure problem in critically ill patients, with mortality rates of around 40.0% and causing long-term morbidity in survivors. ARDS has been defined as Berlin-Definition and may modify in resource-constrained settings. Various etiologies can induce lung inflammation and leading to the diffuse pulmonary edema that defines ARDS. The main treatment consists of specific correct lung injury etiology and support in critical illness that must be undertaken simultaneously. Several supportive strategies: lung-protective ventilation, prone positioning and neuromuscular blocking agent in order to facilitate mechanical ventilation, show a significant reduction in mortality. ARDS management in present day, shifting toward prevention and early treatment, is likely to reduce the incidence and burden of this syndrome. Keywords: acute respiratory distress syndrome, pulmonary edema, treatment